Development of Taekwondo Athlete Achievement in Semarang Regency - Siti Mutmainah; Said Juanidi (Universitas Sriwijaya, 2023)
This study aims to determine 1) the stages of implementation of achievement development at Dojang Spartan, 2) the process of recruiting coaches and athletes, 3) the implementation of training programs, 4) funding and organization of Dojang Spartan, 5) the condition of facilities and infrastructure of Dojang Spartan. The method used in this study uses descriptive research with a qualitative approach. Data collection techniques using observation, interviews, and documentation. The sample selection used a purposive sampling technique with nine informants, one person in charge, two coaches and six athletes. Data analysis in this study used data reduction, data presentation, then drawing conclusions or verification. The results of this study include: 1) the stages of implementing Dojang Spartan training are quite good, 2) the recruitment of trainers and athletes has not been carried out by selection tests to be used as future consideration and evaluation material, 3) the Dojang Spartan coaching training program is still abstract following the existing championship schedule and the training program has not been written, 4) the source of funds for Dojang Spartan is based on contributions made by parents according to the agreement, and the person in charge will regulate the management of the organization, 5) the condition of Dojang Spartan's facilities and infrastructure is still quite decent and needs additions. The conclusion of this study shows that the achievement development of Dojang Spartan taekwondo athletes is going quite well. It is hoped that further research will be able to discuss all components supporting the development of taekwondo sports achievement.